Ethnophysics-Based Heat Transfer Analysis of Lemang Plaho for Contextual Physics Learning - Dwitri Pilendia; Bambang Hariyadi; Pinta Murni; Muhammad Naswir (Equator Science Journal, 2026)
Ethnophysics research on traditional foods has frequently focused on identifying science concepts, while the thermal mechanisms and empirical indicators of doneness embedded in cultural practices remain less systematically explained. This study analyzes the production of Lemang Palho in Siulak Mukai District, Kerinci Regency, as a bamboo-based traditional thermal system and examines its contribution to contextual physics learning through indigenous science integration. A descriptive qualitative design with an ethnophysics perspective was employed. Data were collected through direct observation, semi-structured interviews with six informants, and documentation, then analyzed using thematic coding involving data condensation, data display, verification, and interpretation. The findings show that Lemang Palho production involves radiation from fire and embers, conduction through the bamboo wall, and convection of water and steam inside a semi-closed bamboo chamber sealed with a banana-leaf stopper. Doneness is influenced by a bamboo diameter of approximately 3–5 cm, inclined bamboo positioning, periodic rotation, stable embers, a burning duration of approximately 2–4 hours, and retained steam moisture. These findings demonstrate that the traditional process of making Lemang Palho can serve as a culturally grounded learning context for explaining temperature, heat transfer, phase change, and food texture transformation. The study further supports the development of physics teaching materials that connect local wisdom with scientific concepts, thereby strengthening culturally responsive science learning and the integration of indigenous knowledge into the physics curriculum.